Treatment of preeclampsia/eclampsia in Peru - Guevara Ríos, Enrique (2015)
Preeclampsia is a disease of pregnancy that affects mother and fetus and is responsiblefor a considerable proportion of maternal and perinatal deaths. It complicates 3 to 22% ofpregnancies and is the second leading cause of maternal death in Peru with 32%, as well asthe leading cause of maternal death at the National Maternal Perinatal Institute with 43%. Areview of new contributions on severe preeclampsia and eclampsia management and treatmentof one of its most serious complications liver rupture are done.Keywords: Preeclampsia, eclampsia, HELLP syndrome.